2005
DOI: 10.1007/bf03324617
|View full text |Cite
|
Sign up to set email alerts
|

Differential risk factors for early and later hospital readmission of older patients

Abstract: In a medicalized population of older people, several risk factors may be identified for 0-1 month and 2-3 month readmission. Besides severe morbidities at discharge, diagnoses and previous hospitalization, pre-admission IADL was an independent risk factor for 2-3 month readmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
4
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 21 publications
4
35
4
4
Order By: Relevance
“…Vascular diseases and particularly heart failure at discharge were associated to readmission, in agreement with previous observations on the predictive role of diseases of the circulatory system [12] and particularly of heart failure [25]. Also liver diseases were associated with readmission, in agreement with a previous study based upon 30-day readmission [7].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Vascular diseases and particularly heart failure at discharge were associated to readmission, in agreement with previous observations on the predictive role of diseases of the circulatory system [12] and particularly of heart failure [25]. Also liver diseases were associated with readmission, in agreement with a previous study based upon 30-day readmission [7].…”
Section: Discussionsupporting
confidence: 91%
“…These findings are broadly consistent with other observations, showing that previous hospital admission, morbidity/comorbidity and also functional disability and length of hospital stay were common risk factors in people aged ≥ 75 years [9]. In some studies, the duration of hospital stay (defined as longer than the 90th percentile of hospital stays or than median or than 3 days) was associated with a higher risk of short term readmission [12,[19][20][21], most likely indicative of the severity of the basic illness. In the present study the duration of hospitalization did not affect the rate of readmission.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…European studies have indicated that approximately 11% of patients may be re-admitted within a month of discharge (Comette et al, 2005). Such patients were excluded from this study.…”
Section: Study Limitationsmentioning
confidence: 99%